Secure Text Encryption in Intranet Using Elliptic Curve Cryptography - Kumari, Arpana; Kapoor, Vivek (International Journal of Computer Sciences and Engineering, 2019)
The intranet-based applications are safe and in-house applications hosted inside the internal network. Internet applications need internet to process client requests from the browser to web server instead they only need internal communication with an internal dedicated server. Most companies like to deploy such applications to keep their sensitive data inside the network. Army organizations are best examples instead to store data at the remote server through the internet, they prefer to use a local server with the intranet. This work observes the need for security inside intranet-based applications. It implies designing intranet application by mitigating issues evolved in existing work. This work proposed to use of Elliptic Curve Cryptography and RC6 algorithms to keep data safe and secure inside the intranet using double layer security mechanism. The complete work will be implemented using Java technology and a small application will be created to evaluate the performance of the proposed solution.